Pengaruh Behavior Based Safety terhadap Medical Waste Management - Pandega, Arif; Shaluhiyah, Zahroh; Widjasena, Baju (Jurnal Promosi Kesehatan Indonesia, 2015)
ABSTRACTInfluence of Behavior Based Safety toward Medical Waste Management As health care institutions, hospitals not only produce regular garbage, but also produces a wide range of waste in the form of liquid, solid and gas. Most of the hospital's medical waste including hazardous waste into categories and some of them belong to the category of infectious very important to be properly managed. This type of research is a quasi experimental study and the experimental desain was non equivalent control group design. Sampling method by insidential sampling, without attention between inclusion and exclusion criteria which obtained a sample of 30 experimental and 30 control samples. The data obtained by using a paired t test and Npar test. Based on the test results of Paired t-test and Npar test obtained between pretest and posttest control group, for the knowledge variable (p-value = 0.326), attitude (p-value = 0.157) and practice (p-value = 0.317) states no significant differences. Between pretest and posttest experimental group, for the knowledge variable (p-value = 0.000), attitude (p-value = 0.000) and practice (p-value = 0.001) states a significant difference.The influence behavior-based safety program on knowledge, attitudes and practices of medical waste management to nurse at ken saras hospital.Key Words : Behavior based safety, huns card, medical waste managementÂ